THEORETICAL DIALOGUE ON SCHOOL FEEDING IN BRAZIL AND MOZAMBIQUE (REMUNOM, 2024)
Objective: to analyze proposals for implementing School Feeding programs in Brazil and Mozambique. Material and methods: An integrative review was carried out with content analysis of policies, programs and strategies to support school feeding in Brazil and Mozambique. Results and discussion: The Brazilian National School Meal Program is regulated by Resolution CD/FNDE No. 06 of May 8, 2020, based on universality and equity, benefiting basic education students in public, philanthropic and community schools in throughout the country. In Mozambique, there is no legal basis for operationalizing the National School Feeding Program, whose objective is to reduce in a sustainable way the negative impact that Food Insecurity and malnutrition have on education. Conclusion: The Brazilian experience in the field of school feeding presents possibilities for improving the implementation of this program in Mozambique. The successful experience of purchasing food from family farming and the inclusion of food and nutritional education in the pedagogical proposal is worth highlighting. There is a need to structure public policies in the area of ​​food and nutrition in Mozambique that serve as a legal basis for the School Food program.